Types of diabetic retinopathy studied by wide field angiography - Maamouri, R.; Falfoul, Y.; Bouraoui, R.; Kortli, M.; Chebil, A.; Fedra, K.; Nafaa, F.; El Matri, K.; El Matri, L. (Acta ophthalmologica (Oxford, England), 2017)
Purpose To evaluate the types of diabetic retinopathy (DR) using a wide field fluorescein angiography and to identify the associated factors. Methods In a retrospective study, consecutive wide‐field angiographs obtained using the Heidelberg Retina Angiograph 2 with a contact lens system Staurenghi were graded in: anterior, posterior or diffuse diabetic retinopathy. Anterior DR was defined if diabetic retinal changes were noted only at the location anterior to the imaginary circle bordered by the Early Treatment Diabetic Retinopathy Study seven‐standard fields. In all patients central foveal thickness was measured on Spectral‐domain optical coherence tomography using Topcon 2000. Results A total of 69 eyes of diabetic patients were included. Diabetic retinopathy was anterior in 12 eyes (17.4%), posterior in 24 eyes (34.8%) and was diffuse in 33 eyes (47.8%). Retinal non perfusion was associated with anterior DR in 17.5%, posterior DR in 2.5% and diffuse DR in 80% of eyes (p < 0.001). Peripheral vessel leakage was present in 14.3% of anterior DR, and in 85.7% of diffuse DR, and none eye in posterior DR (p < 0.001). The average of central foveal thickness was 232 μm in anterior DR, 303 μm in posterior DR and 459 μm in diffuse DR (p = 0.01). No correlation was found between types of DR and age (p = 0.22), sex (p = 0.2), arterial hypertension (p = 0.12), cardiopathy (p = 0.16), nephropathy (p = 0.16) and dyslipidemia (p = 0.07). Conclusions This study highlighted that diffuse DR was significantly associated with retinal non perfusion and macular edema. Posterior DR was less associated with retinal non perfusion and peripheral vessel leakage. Eyes with anterior and diffuse DR are at greater risk of ocular complications, needing more clinical monitoring.